Matrix Metalloproteinases, T Cell Homing and β-Cell Mass in Type 1 Diabetes - Savinov, Alexei Y. (2009)
The pathogenesis of type 1 diabetes begins with the activation of autoimmune T killer cells and is followed by their homing into the pancreatic islets. After penetrating the pancreatic islets, T cells directly contact and destroy insulin-producing β cells. This review provides an overview of the dynamic interactions which link T cell membrane type-1 matrix metalloproteinase (MT(1)-MMP) and the signaling adhesion CD(44) receptor with T cell transendothelial migration and the subsequent homing of the transmigrated cells to the pancreatic islets. MT(1)-MMP regulates the functionality of CD(44) in diabetogenic T cells. By regulating the functionality of T cell CD(44), MT(1)-MMP mediates the transition of T cell adhesion to endothelial cells to the transendothelial migration of T cells, thus, controlling the rate at which T cells home into the pancreatic islets. As a result, the T cell MT(1)-MMP-CD(44) axis controls the severity of the disease. Inhibition of MT(1)-MMP proteolysis of CD(44) using highly specific and potent synthetic inhi-bitors, which have been clinically tested in cancer patients, reduces the rate of transendothelial migration and the homing of T cells. Result is a decrease in the net diabetogenic efficiency of T cells and a restoration of β cell mass and insulin production in NOD mice. The latter is a reliable and widely used model of type I diabetes in humans. Overall, existing experimental evidence suggests that there is a sound mechanistic rationale for clinical trials of the inhibitors of T cell MT(1)-MMP in human type 1 diabetes patients.